A Study on Attitudes and Behavior of Students at Sekolah Kebangsaan Parit Raja Toward Recycling - Muhamad Seth, Nur Syuhada; DAUD, ZAWAWI (Recent Trends in Civil Engineering and Built Environment, 2021)
The population growth has led to a notable increase in the generation of solid waste. The rapidly changing lifestyle is the factor that creates waste at an alarming rate. Therefore, recycling can be considered as one of the best alternatives to deal with the problem of waste disposal.  The aim of this study is to determine the recycling awareness among fourth to sixth grade student in Sekolah Kebangsaan Parit Raja and identify student’s behaviors and attitudes towards recycling and on how student manage their waste in their daily life. The study employs qualitative research approach in which the questionnaires are distributed among students through Google Form platform. In this study, a sample size of 40 students will be selected at random. The respondents were students aged between 10 and 12 years old at Sekolah Kebangsaan Parit Raja. Students answered a series of questionnaires that were given to them. The data obtained is then analyzed by using descriptive analysis and Statistical Package for the Social Sciences (SPSS).  At the conclusion, the data were tabulated and evaluated to address the principal question of what the attitudes and behaviors of primary school students relative to recycling. This study is excellent starting point to be an assist in developing a sense of responsibility in the student’s efforts towards recycling. Future research is recommended to focus on reaching a bigger sample size and to measure actual recycling attitude and behavior by means of an observational study.